Nomadic furniture : D-I-Y projects that are lightweight and light on the environment - Hennessey, James; Papanek, Victor J. (Atglen : Schiffer publishing, 2008)
Practical furniture designs that are "recyclable, reusable, collapsible, inflatable, stackable, foldable, and disposable"--Foreword. Two previously published volumes in one.
Previously published as: Nomadic furniture (2 v.). 1973-1974.
boek